Death on the Nile [videorecording] the struggle for peace and the assassination of Anwar Sadat - Jessup, Ted.; Westin, AV. ([S.l.] ABC News, 1988)
The story of Egyptian President Anwar Sadat who turned his back on history and wishes of the nation he led to begin the struggle for peace in the Middle East, and lost his life in the process, cut down by assassin's bullets.
Narrator, Peter Thomas.
Keywords: Sadat, Anwar -- 1918-1982.; Sadat, Anwar -- Assassination. -- 1918-1982.; Israel-Arab conflict; Jewish-Arab relations -- 1973-; Presidents -- Egypt